1999
DOI: 10.1016/s0378-1097(99)00522-4
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization analysis of the gene encoding a hemolysin (suilysin) of Streptococcus suis type 2: evidence for the absence of the gene in some isolates

Abstract: A hemolysin gene was cloned from a virulent strain of Streptococcus suis type 2 strain 1933. Analysis of the gene and its product revealed that it is identical to a previously reported hemolysin (suilysin) of S. suis type 2. Southern hybridization analysis of the digested total genomic DNA from S. suis with the cloned hemolysin DNA sequences as probe indicated that the hemolysin gene is present as a single copy on the genome. Genomic DNA of 63 isolates of S. suis encompassing all known serotypes were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 19 publications
(26 reference statements)
1
22
0
Order By: Relevance
“…A gene encoding suilysin (sly) has been cloned and sequenced (30), and the absence of sly in some S. suis strains was demonstrated by PCR using different sets of primers and/or by Southern hybridization analysis using cloned or amplified sly as a probe (24,30). In this study, using 40 field isolates and 28 serotype reference strains, we analyzed the sly region and the corresponding chromosomal region of the strains lacking sly in order to provide additional knowledge about the acquisition and intraspecies transfer of genes in this bacterium.…”
mentioning
confidence: 99%
“…A gene encoding suilysin (sly) has been cloned and sequenced (30), and the absence of sly in some S. suis strains was demonstrated by PCR using different sets of primers and/or by Southern hybridization analysis using cloned or amplified sly as a probe (24,30). In this study, using 40 field isolates and 28 serotype reference strains, we analyzed the sly region and the corresponding chromosomal region of the strains lacking sly in order to provide additional knowledge about the acquisition and intraspecies transfer of genes in this bacterium.…”
mentioning
confidence: 99%
“…However, the absence of these proteins in some virulent strains may preclude the routine use of these tests. Moreover, in a previous study we showed that these proteins were present neither in all S. suis strains nor in all virulent European strains (5,19 20). This method was very attractive, but it was only applied to detect or characterize S. suis from pure cultures.…”
Section: Discussionmentioning
confidence: 99%
“…This serotype was also isolated from nursery pigs with serious cases of meningitis on a Canadian farm (9). Some S. suis strains isolated from healthy carrier pigs (particularly in ton- (19,30). However, the absence of these proteins in some virulent strains may preclude the routine use of these tests.…”
Section: Discussionmentioning
confidence: 99%
“…The strains were screened for the presence of the suilysin gene (sly) essentially as described previously (12).…”
Section: Methodsmentioning
confidence: 99%